El proyecto simondoniano : la individuación del ser en devenir (2017)
ABSTRACT: This paper introduces the proposal of the philosopher Gilbert Simondon about the individuation process, according to which the being is in the process of becoming and can be out of phase to solve his tensions and give rise to physical or living individuals that constitute a system and go through a series of metastable equilibria. In addition, as a clear example of a form of transindividual individuation (referred to as the human being), the inventiveness is mentioned, which occurs thanks to the information that the individual acquires and recovers through imagination. This imagination integrates perception and affectivity and allows creating new norms or mechanisms setting them up in the becoming. Finally, other perspectives of individuation are shown from different authors and are contrasted against Simondon’s proposal.